Novas ferramentas terapêuticas contra a convulsão e o comportamento tipo depressivo: ensaios pré-clínicos com açaí clarificado - MONTEIRO, José Rogério Souza (Universidade Federal do Pará, 2017)
Açai (Euterpe oleracea Mart.) Is a typical northern palm of Brazil, rich in phenolics and anthocyanins, substances with high antioxidant activity, anti-inflammatory and proven beneficial health effects. Oxidative stress and inflammation are involved in the generation and propagation of seizures, main clinical feature of epilepsy, and in the pathogenesis of depression. In this work we investigated the potential neuroprotective effect, anticonvulsant and antidepressant commercial samples of clarified açaí (CA). Only four doses of CA were enough to increase latencies for myoclonic and tonic-clonic seizures and to reduce the total duration of tonic-clonic seizures induced Pentylenetetrazole (PTZ). Eletrocorticográfics changes induced by PTZ were prevented significantly by CA. In the depressive-like behavior model induced by lipopolysaccharide (LPS), CA decreased immobility time and increased significantly the sucrose consumption of animals, indicating that the CA has preventive activity on the appearance of behaviors which are characteristic of clinical depression. Both the PTZ model as LPS CA exhibited potent preventive activity against the oxidative stress. CA prevented lipid peroxidation and elevated nitrite levels in the cerebral cortex, hippocampus, striatum and prefrontal cortex. These results demonstrate for the first time that acai is a fruit that exerts potent protective activity against the development of seizures, the depressive-like behavior and oxidative stress, which is an additional protection for individuals who consume this fruit.